Adaptive Educational Technologies for Literacy Instruction 2016
DOI: 10.4324/9781315647500-15
|View full text |Cite
|
Sign up to set email alerts
|

Computer-Assisted Research Writing in the Disciplines

Abstract: It is arguably very important for students to acquire writing skills from kindergarten through high school. In college, students must further develop their writing in order to successfully continue on to graduate school. Moreover, they have to be able to write good theses, dissertations, conference papers, journal manuscripts, and other research genres to obtain their graduate degree. However, opportunities to develop research writing skills are often limited to traditional student-advisor discussions (Pearson… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
3
2
2

Relationship

3
4

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 26 publications
0
4
0
Order By: Relevance
“…The results of their study suggested that the Mover could be used to help users, particularly L2 scientists and engineers, better understand and construct research papers in different fields and disciplines. Another recent development in the automated move-based technologies is the Research Writing Tutor, developed by Cotos (2014Cotos ( , 2016 and her colleagues (Cotos, Huffman, & Link, 2015). The Research Writing Tutor is a pedagogical tool for teaching and learning disciplinary research article writing, which aims to advance genre-based writing instruction to the next level by incorporating an automated writing evaluation program (i.e., the Research Writing Tutor identifies move and step boundaries automatically and uses them as criteria for automated feedback).…”
Section: Corpus Use In Genre-based Writing Pedagogymentioning
confidence: 99%
“…The results of their study suggested that the Mover could be used to help users, particularly L2 scientists and engineers, better understand and construct research papers in different fields and disciplines. Another recent development in the automated move-based technologies is the Research Writing Tutor, developed by Cotos (2014Cotos ( , 2016 and her colleagues (Cotos, Huffman, & Link, 2015). The Research Writing Tutor is a pedagogical tool for teaching and learning disciplinary research article writing, which aims to advance genre-based writing instruction to the next level by incorporating an automated writing evaluation program (i.e., the Research Writing Tutor identifies move and step boundaries automatically and uses them as criteria for automated feedback).…”
Section: Corpus Use In Genre-based Writing Pedagogymentioning
confidence: 99%
“…advancement in this direction is using move-annotated corpus data to train genre-based automated writing evaluation and feedback technology (Cotos, 2016).…”
mentioning
confidence: 99%
“…Following Swales's (1990) move analysis approach and drawing on his CARS model, the researchers developed a comprehensive introduction-method-resultsdiscussion/conclusion (IMRD/C) move/step framework (see Figure 1 below from Cotos, Huffman, & Link, 2015). This framework was then applied to the development of different technical affordances of the RWT (Cotos, 2016).…”
Section: Research Writing Tutormentioning
confidence: 99%
“…A number of studies on usefulness and effectiveness have been conducted to inform RWT's iterative development and explore how RWT impacts students and their research writing. Empirical evidence indicates that students' interaction with this tool has a positive impact on cognition, revision strategies, learning of genre conventions, development of genre knowledge, writing improvement, and motivation (Cotos, 2016;Cotos, Huffman, & Link, 2020;. While RWT was initially designed to complement graduate writing pedagogy, it has been used in different learning environments, such as peer writing groups, one-on-one consultations with writing tutors, and graduate writing workshops.…”
Section: Figure 2 Screenshot Exemplifying the Video Presentation Of Move-specific Content In The Learning Module Of Rwtmentioning
confidence: 99%